A Mobile App-Based Peer Assessment for Problem-Based Learning Groups - Melissa, Mohammad Hirman; Noor Alamshah, Bolhassan; Nurfauza, Jali; William Lim, Kiong Seng (2025)
Background: Problem-Based Learning (PBL) is the most significant innovation of the last 60 years that promotes active and self-directed learning through problem solving and teamwork. Assessment of these learning outcomes may involve a combination of self, peer, and facilitator assessments. Our school practices facilitator grading but observed non-uniformity across groups. We complemented facilitator grading with peer evaluation to enhance students' evaluative and reflective skills. The students used a specially developed mobile app, PeerA app, to conduct weekly peer assessments during their PBL sessions. Peer evaluation is notably challenged with problems of friendship marking and anonymity, making it questionable in terms of its reliability and accuracy. Meanwhile, digital tools can offer improved efficiency, fairness, and confidentiality in peer assessment and are increasingly used in education. Thus far, there is no report on online peer assessment tools in PBL settings.